Change in Dehydrogenase Activity, Hormone Content and Lipoperoxidation State in Allogeneic Placenta Depending Upon Low Temperature Effect - Grischenko, V. I.; Shepit’ko, V. I.; Strona, V. I.; Yurchenko, T. M.; Ryazantsev, V. V.; Tsebrzhinsky, O. I. (Problems of Cryobiology and Cryomedicine, 2004)
The paper presented the data on metabolic alterations in placenta tissue during its hypothermic storage. The most manifested metabolic changes in placenta tissue were noted when being stored for 24hrs (4°C), 24hrs (-196°C) and further storage for 1 year (-20°C).